Motor neuron-like NSC-34 cells as a new model for the study of vitamin D metabolism in the brain. Issue 158 (April 2016) - Almokhtar, Mokhtar; Wikvall, Kjell; Ubhayasekera, S.J. Kumari A.; Bergquist, Jonas; Norlin, Maria
Highlights: Altered vitamin D levels have been linked to several CNSdisorders. Mechanisms for regulation of vitamin D levels in brain cells are unknown. The current study explores the properties of motor-neuron NSC-34 cells. NSC-34 cells express many vitaminD-related genes and metabolize vitamin D compounds. NSC-34 cells are a new tool of interest for study of vitamin D regulation in the CNS. Abstract: Vitamin D3 is a pro-hormone, which is sequentially activated by 25- and 1α-hydroxylation to form 25-hydroxyvitamin D3 [25(OH)D3 ] and 1α, 25-dihydroxyvitamin D3 [1α, 25(OH)2 D3 ], respectively. Subsequent inactivation is performed by 24-hydroxylation. These reactions are carried out by a series of CYP450 enzymes. The 25-hydroxylation involves mainly CYP2R1 and CYP27A1, whereas 1α-hydroxylation and 24-hydroxylation are catalyzed by CYP27B1 and CYP24A1, respectively, and are tightly regulated to maintain adequate levels of the active vitamin D hormone, 1α, 25(OH)2 D3 . Altered circulating vitamin D levels, in particular 25(OH)D3, have been linked to several disorders of the nervous system, e.g., schizophrenia and Parkinson disease. However, little is known about the mechanisms of vitamin D actions in the neurons. In this study, we examined vitamin D metabolism and its regulation in a murine motor neuron-like hybrid cell line, NSC-34. We found that these cells express mRNAs for the four major CYP450 enzymes involved in vitamin D activation and inactivation, and vitamin D receptor (VDR) that mediates vitamin D actions. We also found high levels of CYP24A1-dependent 24, 25-dihydroxyvitamin D3 [24, 25(OH)2 D3 ] production, that was inhibited by the well-known CYP enzyme inhibitor ketoconazole and by several inhibitors that are more specific for CYP24A1. Furthermore, CYP24A1 mRNA levels in NSC-34 cells were up-regulated by 1α, 25(OH)2 D3 and its synthetic analogs, EB1089 and tacalcitol. Our results suggest that NSC-34 cells could be a novel model for the studies of neuronal vitamin D metabolism and its mechanism of actions.